Association between internet use and depression among the middle-aged and elderly adults with multimorbidity in China: do gender differences exist? - Zhang, Jiao; Jia, Yuheng; Hong, Lixin; Zhang, Yixin; Li, Lihua; Tian, Kan (Frontiers in Psychiatry, 2025)
ObjectivesInternet use and the results of mental health are related. Numbers of studies presented the association between Internet use and depression, and the middle-aged and elderly adults with multimorbidity are of concern. The study aimed to explore the relationship between Internet use and depression in middle-aged and elderly adults with multimorbidity.MethodsWe selected 2550 respondents aged 45 years and above with multimorbidity from the China Health and Retirement Longitudinal Study (CHARLS) 2018 database. Logistic regression models were constructed to examine the effects of Internet use on depression, as well as comparing gender differences. Meanwhile, propensity score matching (PSM) was used to test the robustness of the results.ResultsOverall, 49.8% of respondents had a risk of developing depression, and 14.9% of the participants used the Internet. Internet use (OR = 0.66, P = 0.002), type of devices (one type: OR = 0.69, P = .011;≥2 types: OR = 0.53, P = 0.03), frequency of Internet use (regularly: OR = 0.67, P = 0.005) were all inversely associated with depression. Significant differences between genders were observed, Internet use was associated with a lower prevalence of depression among men, while the association was not statistically significant among women.ConclusionsThere is a significantly negative association between Internet use and depression in the middle-aged and elderly adults with multimorbidity in China, and this relationship varies across different genders. This suggests that Internet use may be a protective factor for depressive symptoms in the older population, offering a guideline for policymakers to develop specific strategies for different genders.